2006
DOI: 10.4049/jimmunol.177.9.5990
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Deletion of Shp2 Tyrosine Phosphatase in Thymocytes Suppresses Both Pre-TCR and TCR Signals

Abstract: It is well known that T cell differentiation and maturation in the thymus is tightly controlled at multiple checkpoints. However, the molecular mechanism for the control of this developmental program is not fully understood. A number of protein tyrosine kinases, such as Zap-70, Lck, and Fyn, have been shown to promote signals required for thymocyte development, whereas a tyrosine phosphatase Src homology domain-containing tyrosine phosphatase (Shp)1 has a negative effect in pre-TCR and TCR signaling. We show i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 34 publications
(38 reference statements)
6
64
2
Order By: Relevance
“…Our findings point to a positive role for SHP2 in certain arms of the FcRI signaling cascade. Consistent with studies of SHP2 in other cell types and pathways (24,47), we find that SHP2 promotes activation of Jnk and Erk MAPKs, Akt and IKK pathways downstream of FcRI. This effect is consistent with elevated Lyn activity and reduced Fyn signaling in SHP2 KO BMMCs.…”
Section: Discussionsupporting
confidence: 76%
“…Our findings point to a positive role for SHP2 in certain arms of the FcRI signaling cascade. Consistent with studies of SHP2 in other cell types and pathways (24,47), we find that SHP2 promotes activation of Jnk and Erk MAPKs, Akt and IKK pathways downstream of FcRI. This effect is consistent with elevated Lyn activity and reduced Fyn signaling in SHP2 KO BMMCs.…”
Section: Discussionsupporting
confidence: 76%
“…50), and B and T lymphocyte attenuator (BTLA; Ref 51). Because SHP-2 has been implicated in both inhibitory (52,53) and stimulatory (54,55) signaling cascades, its contribution to CEACAM1-dependent effects must still be defined.…”
Section: Discussionmentioning
confidence: 99%
“…One of the first clues to reconcile the antibody-specific differences was the demonstration by Wang et al that their anti-VISTA antibody shows almost undetectable levels of VISTA after T cell activation, while Flies et al observed substantial elevation of PD-1H on both CD4 + and CD8 + T cells after activation. These fickle antibodies highlight what students of immunology have learned from mice: it is not a good idea to discern biology of a molecule by its antibodies (7)(8)(9)(10). In this issue, Flies et al (11) elucidate the biological function of PD-1H using mice with targeted mutation of the gene encoding PD-1H.…”
Section: Remaining Questionsmentioning
confidence: 99%